Irradiation potentiates p53 phosphorylation and p53 binding to the promoter and coding region of the TP53 gene - Legartová, Soňa; Fagherazzi, Paolo; Goswami, Pratik; Brazda, Vaclav; Lochmanová, Gabriela; Koutná, Irena; Bártová, Eva (Biochimie, 2023)
An essential factor of the DNA damage response is 53BP1, a multimeric protein that inhibits the resection-dependent double-strand break (DBS) repair. The p53 protein is a tumor suppressor known as a guardian of the genome. Although the interaction between 53BP1 and its p53 partner is well-known in regulating gene expression, a question remains whether genome injury can affect the interaction between 53BP1 and p53 proteins or p53 binding to DNA. Here, using mass spectrometry, we determine post-translational modifications and interaction properties of 53BP1 and p53 proteins in non-irradiated and γ-irradiated cells. In addition, we used Atomic Force Microscopy (AFM) and Fluorescent Lifetime Imaging Microscopy combined with Fluorescence Resonance Energy Transfer (FLIM-FRET) for studies of p53 binding to DNA. Also, we used local laser microirradiation as a tool of advanced confocal microscopy, showing selected protein accumulation at locally induced DNA lesions. We observed that 53BP1 and p53 proteins accumulate at microirradiated chromatin but with distinct kinetics. The density of 53BP1 (53BP1pS1778) phosphorylated form was lower in DNA lesions than in the non-specified form. By mass spectrometry, we found 22 phosphorylations, 4 acetylation sites, and methylation of arginine 1355 within the DNA-binding domain of the 53BP1 protein (aa1219-1711). The p53 protein was phosphorylated on 8 amino acids and acetylated on the N-terminal domain. Post-translational modifications (PTMs) of 53BP1 were not changed in cells exposed to γ-radiation, while γ-rays increased the level of S6ph and S15ph in p53. Interaction analysis showed that 53BP1 and p53 proteins have 54 identical interaction protein partners, and AFM revealed that p53 binds to both non-specific and TP53-specific sequences (AGACATGCCTA GGCATGTCT). Irradiation by γ-rays enhanced the density of the p53 protein at the AGACATGCCTAGGCATGTCT region, and the binding of p53 S15ph to the TP53 promoter was potentiated in irradiated cells. These findings show that γ-irradiation, in general, strengthens the binding of phosphorylated p53 protein to the encoding gene.
Keywords: nádorový supresorový protein p53; poškození DNA; geny p53; DNA; Phosphorylation; DNA Damage; DNA Repair; Genes, p53; fosforylace; oprava DNA; Tumor Suppressor Protein p53